PENGARUH SUMBER DAYA MANUSIA, SISTEM OPERASIONAL, DAN ADMINISTRASI KANTOR TERHADAP TEKNOLOGI ADMINISTRASI PERUSAHAAN - Fika Putri Mulyawati; Wolor, Christian Wiradendi; Marsofiyati (Sehati Abdimas, 2023)
Researchers conducted research on the influence of human resources, operational systems, and office administration on company administration technology. This research aims to determine whether there is a negative and significant influence between human resources, operational systems and office administration on company administration technology. This research uses quantitative research methods. Data collection was carried out through questionnaires distributed to company employees who had experience in implementing administrative technology. In addition, interviews and observations were also conducted to gain a deeper understanding of the factors that influence the implementation of administrative technology. Research is measured using a Likert scale from one to five. The data analysis techniques used in this research are: Outer Model with convergent validity calculations, Discriminant validity, AVE (Average Variance Extracted), Composite validity, Cronbach's Alpha and Inner Model with Path coefficient calculations, Model feasibility test, VIF (Variance Inflation Factor), Total indirect effects, Specific indirect effects using SmartPLS 4 software. The research results show that: (1) Skilled and trained human resources have a positive impact on the application of administrative technology; (2) An efficient operational system also has a significant contribution in supporting administrative technology; (3) Good office administration can facilitate the integration of administrative technology into the company's business processes.